From Shock to Strength: Psychological Capital Mediates the Impact of Reverse Culture Shock on Distress - saputra, nofrans eka; Ekawati, Yun Nina; Periantalo, Jelpa; Ulivia, Ayu; Rillis, Vicky (Universitas Ahmad Dahlan, 2025)
Reverse Culture Shock (RCS) is a psychosocial challenge experienced by individuals returning to their home country after participating in a program abroad. This study aims to examine the effect of RCS on psychological distress, with psychological capital acting as a mediating variable.This research employed a quantitative survey design and utilized Structural Equation Modeling (SEM) for data analysis. Data were collected using the DASS-21 scale, the Psychological Capital (PsyCap) scale, and the Reverse Culture Shock scale. The population consisted of 1,980 awardees of the 2023 Indonesian International Student Mobility Awards (IISMA), with a sample of 316 students selected through random sampling. The results revealed that RCS had a significant negative effect on psychological capital (β = -0.427; p < .001) and a significant positive effect on psychological distress (β = 0.348; p < .001). Psychological capital also had a significant negative effect on psychological distress (β = -0.368; p < .001). Furthermore, a partial mediation effect of psychological capital was found in the relationship between RCS and psychological distress (β = 0.157; VAF = 31.1%; p < .01). These findings suggest that higher levels of RCS are associated with greater psychological distress, but psychological capital can buffer this negative impact. The study highlights the importance of psychological interventions that strengthen internal psychological resources to support re-adaptation after cross-cultural experiences.